Comfort, well-being and quality of life: discussion of the differences and similarities among the concepts - Pinto, Sara (2017)
Aim: To analyze the differences and similarities of the concepts of comfort, well-being and quality of life (QoL). Methods: Review of concept analysis research on PubMed, Cinahl (full text) and Scielo, using the search terms “Comfort”, “Well-being”, “Quality of Life” and “Concept Analysis”. Results: Eighteen studies were included. Comfort is a broader holistic concept while well-being is mainly related to psycho-spiritual dimensions. QoL reflects the individual perception of satisfaction with life.Conclusions: The concepts are not surrogate terms, but related concepts sharing common attributes. Caution should be taken in further research, particularly as regards the correct use and framing of the concepts.